1999
DOI: 10.1039/a901185d
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state electrogenerated chemiluminescence in sol–gel derived monoliths

Abstract: Stable solid-state electrogenerated chemiluminescence has been achieved by trapping the chemiluminescent precursors, ruthenium(ii) tris(bipyridine) and tripropylamine, in a porous silicate host matrix prepared by the sol-gel process and exciting them electrochemically via an immobilized microelectrode assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
(19 reference statements)
2
25
0
Order By: Relevance
“…While these devices have no direct analytical use there has been significant interest in the area of steady-state electrochemiluminescence for large area emissive panels and displays with low operating voltages. 97 Collinson and Martin 97,98,131 investigated sol-gel entrapped tris(2,29-bipyridyl)ruthenium(II) with oxalate and various amines. The use of microelectrodes decreased consumption of the reductant and provided a steady state flux of reagents to the electrode surface.…”
Section: Light Emitting Devicesmentioning
confidence: 99%
“…While these devices have no direct analytical use there has been significant interest in the area of steady-state electrochemiluminescence for large area emissive panels and displays with low operating voltages. 97 Collinson and Martin 97,98,131 investigated sol-gel entrapped tris(2,29-bipyridyl)ruthenium(II) with oxalate and various amines. The use of microelectrodes decreased consumption of the reductant and provided a steady state flux of reagents to the electrode surface.…”
Section: Light Emitting Devicesmentioning
confidence: 99%
“…Recent trends involve either the use of silica sol as a nanoglue to create guest-host composite aerogels [215,216], or the covalent modi®cation of micro-or mesoporous silicates with new ligands, molecular recognition centers, dyes, or chemiluminescent molecules [136,168,217]. Even if electrosynthesis of metal oxides and hydroxides is an emerging technique in materials science [218], only few examples are available dealing with electrochemical methods to generate sol-gel ®lms [219,220].…”
Section: Recent Trends ± Novel Approachesmentioning
confidence: 99%
“…For example Peng et al [202] reported the fabrication of an amperometric sensor for Escherichia coli, based on the adsorption of bilayer vesicles (liposomes) on a sol-gel silica ®lm coated on glassy carbon. Another promising research direc-tion involving the implication of silica-based materials in electroanalysis is the design of reagentless electrochemiluminescence (ECL)-based sensors [178], as well as solidstate ECL sensors [168], by exploiting the ability of incorporating electroactive dyes or chromophores into sol-gel silica. In this application, the silica ®lm is essential to prevent fouling of the electrode surface, which is a common problem associated to the amperometric detection of proteins.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 2 more Smart Citations